MENUMBUHKAN RASA EMPATI MAHASISWA KE SESAMA MELALUI PROGRAM KUNJUNGAN KE PANTI ASUHAN AL MUZAKKI - Novita, Novita (Komunitas Manajemen Kompetitif, 2024)
Empathy contributes to the formation of a strong, positive and healthy character. It helps individuals to live in a more harmonious way with others, as well as encouraging them to be part of the solution to various social challenges. One of the efforts made to foster empathy is carried out by students taking character development courses by visiting orphanages. This study proves the effect of visits to orphanages on empathy. The method used is a survey method by taking a sample of 40 people based on the number of indicators used as many as 8 indicators multiplied by five. Through an online questionnaire, the data was analyzed using quantitative methods. The results of the study prove that visits to orphanages have a positive and significant effect on students' empathy.